Highly active nanostructured Co3O4 catalyst with tunable selectivity for liquid phase air oxidation of p-cresol - Kshirsagar, Vikas S.; Vijayanand, Subramanian; Potdar, Hari S.; Joy, Pattayil Alias; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chemistry Letters, 2008)
This is a first report of highly efficient heterogeneous nanostructured Co3O4 catalyst (6-8 nm) having high surface area (95 m(2)/g) developed for selective liquid phase air oxidation of p-cresol under atmospheric pressure conditions.